Banking Stability and Shadow banking: "New Overview for the United States" - José Alejandro Fernández Fernández (Australasian Accounting, Business and Finance Journal, 2022)
This paper analyses commercial banking and shadow banking, with the intention of understanding different channels of instability that can occur through both types of banking for the United States. The work is pioneering a comprehensive vision of shadow banking and its interrelation with commercial banking. The results of the work are designed to encourage reflection on possible mediums to promote the stability of shadow banking, through new risk indicators. Finally, these indicators are tested using machine learning techniques.
Keywords: shadow banking; bank stability; canonical analysis; random forest.